2017
DOI: 10.1177/1753944717723311
|View full text |Cite
|
Sign up to set email alerts
|

Do ANGPTL-4 and galectin-3 reflect the severity of coronary artery disease?

Abstract: In conclusion, ANGPTL-4 and galectin-3 do not appear to have a promising role for assessing the severity of CAD. Nevertheless these biomarkers do warrant further exploration in improving the management of CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Another study indicated that ANGPTL8 concentration exhibited no significant difference between CAD group and non-CAD group [ 19 ] and ANGPTL8 levels were not a factor for CAD in the multivariate analysis [ 20 ], which is consistent with our results. No significant association was found between ANGPTL4 level and angiographically characterized coronary atherosclerosis and severity of CAD [ 21 , 22 ]. Consistent with previous reports, our study did not find a significant association between ANGPTL4 and CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Another study indicated that ANGPTL8 concentration exhibited no significant difference between CAD group and non-CAD group [ 19 ] and ANGPTL8 levels were not a factor for CAD in the multivariate analysis [ 20 ], which is consistent with our results. No significant association was found between ANGPTL4 level and angiographically characterized coronary atherosclerosis and severity of CAD [ 21 , 22 ]. Consistent with previous reports, our study did not find a significant association between ANGPTL4 and CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the circulating level of Gal-3 was significantly higher in patients with a myocardial infarction (MI) than in healthy control subjects [ 12 ]. Whereas others [ 13 ] did not observe a significant difference in Gal-3 concentration between these groups of patients. Recently published data suggest that Gal-3 is an independent risk factor of a coronary artery disease occurrence [ 12 ].…”
Section: Introductionmentioning
confidence: 58%
“…There are limited data on this biomarker in the ACS population. In addition, some authors suggest that Gal-3 does not appear to have a promising role for assessing the severity of CAD [ 13 ]. Our present research revealed that in the study group of MI patients, the Gal-3 concentration was significantly higher than in the group of patients without symptomatic CAD.…”
Section: Discussionmentioning
confidence: 99%
“…The current study results may propose that Gal-3 as a major inflammatory marker, can have a substantial role in the pathogenetic process of plaque disturbance and ACS. Compared to patients with normal CA, earlier studies reported significantly high Gal-3 concentrations among CAD cases (11,(15)(16)(17)(18)(19)(20)(21)(22) , CCS (17,23&24) , ACS (25) , NSTEMI (16,17&26) , STEMI (17,27&28) , and premature myocardial infarction (29) . On the other hand, compared to patients with CCS, earlier studies demonstrated that Gal-3 values were significantly greater among those with ACS (16,24,30&31) and STEMI (17) .…”
Section: Discussionmentioning
confidence: 94%